Monitoring Information System of Supplementary Feeding Program for Stunted Toddlers at Posyandu Matahari - Amelia Nur Fadhila; Rina Firliana; Aidina Ristyawan (Proceeding International Conference on Digital Education and Social Science, 2025)
Stunting is a serious health issue in Indonesia, with a prevalence reaching 21.6% in 2022. The Supplementary Feeding Program at Posyandu Matahari, Bangkok Village, faces challenges in monitoring daily consumption, specifically in ensuring that the food is consumed by toddlers as recommended. The objective of this research is to develop a Supplementary Feeding Program monitoring information system capable of automatically classifying nutritional status, storing monitoring data, and generating systematic reports. This study is a system development research focused on stunted toddlers aged 6-59 months. The method employed is the prototyping method, which includes user requirements identification, prototype creation, system coding, testing, and implementation. The results demonstrate that the information system integrates daily Supplementary Feeding Program consumption data with digital anthropometric records. This system enables staff to analyze nutritional status developments in real-time and prepare monitoring reports more accurately. The study concludes that the implementation of a monitoring information system can address Supplementary Feeding Program consumption non-compliance and simplify reporting bureaucracy, thereby supporting the optimization of the Supplementary Feeding Program in improving the nutritional status of toddlers at Posyandu Matahari.